Transparent design in higher education teaching and learning : a guide to implementing the transparency framework institution-wide to improve learning and retention - Winkelmes, Mary-Ann, 1964-; Boye, Allison, 1977-; Tapp, Suzanne, 1966-; Felten, Peter; Finley, Ashley P. (Ashley Paige) (New pedagogies and practices for teaching in higher education series., 2019)
This book offers a comprehensive guide to the Transparency in Learning and Teaching (TILT) framework that has convincingly demonstrated that implementation increases retention and improved outcomes for all students. Its premise is simple: to make learning processes explicit and equitably accessible for all students. Transparent instruction involves faculty/student discussion about several important aspects of academic work before students undertake that work, making explicit the purpose of the work, the knowledge that will be gained and its utility in students'lives beyond college; explaining the tasks involved, the expected criteria, and providing multiple examples of real-world work application of the specific academic discipline. The simple change of making objective and methods explicit - that faculty recognize as consistent with their teaching goals - creates substantial benefits for students and demonstrably increases such predictors of college students'success as academic confidence, sense of belonging in college, self-awareness of skill development, and persistence. This guide presents a brief history of TILT, summarizes both past and current research on its impact on learning, and describes the three-part Transparency Framework (of purposes, tasks and criteria). The three sections of the book in turn demonstrate why and how transparent instruction works suggesting strategies for instructors who wish to adopt it; describing how educational developers and teaching centers have adopted the Framework; and concluding with examples of how several institutions have used the Framework to connect the daily work of faculty with the learning goals that departments, programs and institutions aim to demonstrate.